Analyzing Product Quality And Promotion On Purchasing Decisions For Charcoal Wood Cv.Tri Karti Mukti - Santo Hegiarto, Aldy; Saeful Hamdani, Yusep (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This study aims to determine what factors can influence purchasing decisions. This study uses two independent variables, namely Product Quality (X1) and promotion (X2), meanwhile, purchasing decisions (Y) are used as the dependent variable. In this study, the authors used descriptive-quantitative research methods, namely researchers trying to make descriptions, images systematically, factually and accurately regarding the relationship between the facts, properties or phenomena studied. The R Square coefficient of 0.760 or 76% indicates that the variables of Product Quality (X1) and promotion (X2), affect the Purchasing Decision variable by 76%, other variables not included in this study have an effect of 24%. Purchasing Decisions simultaneously or simultaneously have a positive effect between Product Quality and promotion with Purchasing Decisions. This is indicated by the calculated F value of 66,320 and significance at <0.001, so that these results indicate that Product Quality and promotion are not simultaneously due to the positive influence of several elements that make a significant contribution to purchasing decisions. keywords: Product Quality, promotion, purchasing decision